2014
DOI: 10.1007/s11277-014-1851-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 20/40/60/80 MHz Channel Access for 80 MHz 802.11ac

Abstract: This paper is to contribute a new dynamic channel access method for wireless local area networks. It allows a station accessing the 80 or 160 MHz channel to capture every idle non-primary 20 MHz channel along with the primary 20 MHz channel, whereas the number of channel configurations in which the station can transmit according to the 802.11ac standard is strictly limited. Simulation results shown in the paper prove the proposed access method to be superior to the method provided by the 802.11ac standard in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The four main enhancements at the PHY layer are the use of 256-QAM, down link multiuser MIMO, up to eight antennas and supports (i 20, i40, 80 and 160 MHz) channels bandwidth [4]. The IEEE 802.11ac supports MIMO with OFDM to increase channel capacity and allows maximum data rates of 693 (1×1 SS) and 6240 (8×8 SS) Mbps [14], [15].…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…The four main enhancements at the PHY layer are the use of 256-QAM, down link multiuser MIMO, up to eight antennas and supports (i 20, i40, 80 and 160 MHz) channels bandwidth [4]. The IEEE 802.11ac supports MIMO with OFDM to increase channel capacity and allows maximum data rates of 693 (1×1 SS) and 6240 (8×8 SS) Mbps [14], [15].…”
Section: Research Methods and Materialsmentioning
confidence: 99%
“…This approach attempts to reduce the performance of bottleneck and scalability problems. Stelter et al [15] designed a dynamic channel access mechanism for IEEE 802.11acbased networks by employing the CCA functionality. Authors in [17] investigate the performance of the dynamic bandwidth channel access operation in IEEE 802.11ac.…”
Section: Existing Approaches and Their Limitationsmentioning
confidence: 99%
“…(ii) Average rate of throughput decrement due to the decrease of DAP: From Fig. 3(b), it can be observed that, for any k stations, with k = [5,10,15,20,25,30], the rate of throughput decrement is the highest when the DAP is reduced to 80m from 160m. As the DAP decreases, the chances of getting inside of the coverage area of the IR of an STA become higher for an AP.…”
Section: Pilot Studymentioning
confidence: 99%
“…Since most previous works addressed the spectral underutilization efficiency problem [9,10], here we present related studies that are most relevant to multichannel access schemes [10][11][12][13][14]. The channel bonding technique has been proposed to work on one wide channel rather than multichannel access because it increases the data rate and supports the high speed of IEEE 802.11 communications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of channel bonding increases delay and resource consumption according to [14,20,21]. Dynamic multichannel access has been proposed to overcome these problems.…”
Section: Literature Reviewmentioning
confidence: 99%